Educators’ Perceptions of Human Trafficking and Implications for Professional Development - Abram, Jason; Rushek, Kelli (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
Around 3.3 million young people are trafficked worldwide, with over half subjected to sexual exploitation (Data and Research on Forced Labour, 2024). However, little research exists on the role of school-based educators in learning about, preventing, and identifying human trafficking. This study examines educators’ knowledge of trafficking both locally and globally. Grounded in critical anti-trafficking frameworks, Schulman’s (1987) framework of teachers’ knowledge, and Bronfenbrenner and Cici’s (1994) Bioecological Model, the study surveyed 205 educators in Central Florida in the United States. Findings show that over 60% had received no training on human trafficking, while 24.3% of those who had training were uncertain about how to report trafficking cases. Educators also expressed a desire for more school-based training and professional development. Implications suggest using critical, pedagogical approaches like Ginwright’s (2018) healing-centred engagement to enhance educators’ understanding and help deter global trafficking networks.